Correlation between English education Students’ Reading Comprehension and Their Writing Skills - Afiz, Andi Muh. Furqan; Korompot, Chairil Anwar; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study was aimed at finding out whether or not there was a correlation between reading comprehension and writing achievement of English Education Study Program Students of the State University of Makassar. The population of the study is all of the fifth semester students while the sample is 38 students using a random sampling technique. The data in this study were collected through two research instruments; a multiple-choice reading comprehension test and a writing test. Pearson product-moment correlation was applied in order to find out the correlation between the variables. The findings of the study showed there was a significant correlation among variables (rxy= .68 > r-table=0.304). Interesting findings in the study indicate some potential variables that could help explain the nature of the reading and writing relationship.